2015
DOI: 10.1038/ncomms7560
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the cloud of diversity reveals complexity and heterogeneity of MRSA carriage, infection and transmission

Abstract: Genome sequencing is revolutionizing clinical microbiology and our understanding of infectious diseases. Previous studies have largely relied on the sequencing of a single isolate from each individual. However, it is not clear what degree of bacterial diversity exists within, and is transmitted between individuals. Understanding this ‘cloud of diversity’ is key to accurate identification of transmission pathways. Here, we report the deep sequencing of methicillin-resistant Staphylococcus aureus among staff and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
144
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(153 citation statements)
references
References 60 publications
(64 reference statements)
2
144
0
Order By: Relevance
“…However, it obviously belonged to the outbreak, suggesting that an LA-MRSA strain colonizing or infecting different sites within the same person may evolve independently over time. Recent reports that applied whole-genome sequencing on multiple colonies from the same person also identified a cloud of diversity among the isolates (21,34,35). These studies were carried out on ST22 and ST239 MRSA isolates, but similar findings might be expected from LA-MRSA.…”
Section: Discussionmentioning
confidence: 68%
“…However, it obviously belonged to the outbreak, suggesting that an LA-MRSA strain colonizing or infecting different sites within the same person may evolve independently over time. Recent reports that applied whole-genome sequencing on multiple colonies from the same person also identified a cloud of diversity among the isolates (21,34,35). These studies were carried out on ST22 and ST239 MRSA isolates, but similar findings might be expected from LA-MRSA.…”
Section: Discussionmentioning
confidence: 68%
“…Finally, we assessed transmission events based on shared spa types between household members. However, recent whole genome sequencing studies have demonstrated that shared spa types may not indicate true transmission events; both false positives and false negatives are possible [46,47]. …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the UK where the use of clindamycin is limited, all EMRSA-15 ermC leader peptides were intact, therefore making these isolates susceptible to clindamycin [21]. The human EMRSA-15 epidemic has also spread into the companion animal population [22,23], with veterinary hospitals also being healthcare settings that may experience high levels of transmission [24]. A c c e p t e d M a n u s c r i p t 12 documented in Portugal, Singapore and Australia [25][26][27].…”
Section: Hospital-associated Meticillin-resistantmentioning
confidence: 99%